1988
DOI: 10.1016/0043-1354(88)90167-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytopathogenicity, immunofluorescence and In situ DNA hybridization as methods for the detection of adenoviruses

Abstract: Three different methods were compared for their et~ciency at detection of adenoviruses. The samples examined for viral analysis consisted of concentrates prepared from raw sewage, chosen as providing a representation of the spectrum of viruses being intestinally shed from a large population at any given time. When using one single cell line, HEp-2, the overall numbers of adenoviruses detected using cytopathogenicity and immunofluorescence were roughly equal. In situ hybridization was approx. 40% more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…60 It has been reported that the number of adenoviruses present in raw primary sludge may exceed that of the enteroviruses by an average factor of 94-fold. 61 It has also been estimated that approximately 80% of the adenoviruses present in wastewater sludges are of serotypes 40 and 41, 61 which cause gastroenteritis.…”
Section: Descriptions Of the Human Enteric Virus Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 It has been reported that the number of adenoviruses present in raw primary sludge may exceed that of the enteroviruses by an average factor of 94-fold. 61 It has also been estimated that approximately 80% of the adenoviruses present in wastewater sludges are of serotypes 40 and 41, 61 which cause gastroenteritis.…”
Section: Descriptions Of the Human Enteric Virus Groupsmentioning
confidence: 99%
“…Use of newer, more rapid, assay methods for detecting human viruses has helped to greatly reduce the second concern. 61 It must also be realized that bacteriophages generally respond very differently from enteric viruses in terms of their inactivation times when exposed to chemical disinfection agents, such as chlorine. Bacteriophages also have the potential to increase their numbers within wastewater sludges if the proper bacterial host organisms are present.…”
Section: B Which Viruses May Be Of Concern In Wastewater?mentioning
confidence: 99%
“…There is little information on the level of adenoviruses in surface and source waters, but they have been found in raw sewage at often greater concentrations than enteroviruses (Irving & Smith 1981;Hurst et al 1988) and they were shown to be more persistent in natural waters than enteroviruses (Enriquez et al 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Enteric adenoviruses are shed in high numbers in the feces (1) and, like NLVs, are typically shed in the feces for long periods, and infection can be caused by low numbers of viral particles (16,22). Enteric adenoviruses have greater environmental stability than other enteric viruses (10), and their presence in sewage and surface water makes them likely contaminants in public water supplies (24,25). Moreover, enteric adenoviruses and NLVs were identified as two of the etiological agents causing acute gastroenteritis in a waterborne outbreak in Finland (30), and waterborne outbreaks of pharyngoconjuctivitis from swimming have been reported for nonenteric adenoviruses (15,35).…”
mentioning
confidence: 99%